2020
DOI: 10.1186/s12876-020-01455-0
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal major papilla morphology can affect biliary cannulation and complications during ERCP, an observational study

Abstract: Background We investigated whether duodenal major papilla morphology could be a risk factor for failure of selective biliary cannulation (SBC) and post endoscopic retrograde cholangiography and pancreatography (ERCP) complications. Methods A prospectively recorded database was reviewed retrospectively. Patients were included if they received therapeutic ERCP and had naïve major duodenal papilla. We used Haraldsson’s classification for papilla morphology, as follows: Regular (Type 1), Small (Type 2), Protrudi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 14 publications
4
20
1
7
Order By: Relevance
“…Un estudio retrospectivo publicado en China en 2020 revela que las papilas tipo 2 y 3 requieren más tiempo para la canulación y tienen una tasa más alta de canulación fallida (12 % y 11,1 %) con respecto a las papilas 1 y 4 (1,7 % y 6,25 %) (13) , a diferencia de nuestros resultados, que muestran que los tipos de papila que requirieron más tiempo de aunque no encontramos asociación entre el tipo de papila y la canulación difícil. Por su parte, los tiempos promedio de canulación mostrados en nuestro estudio fueron mayores, sobre todo para el tipo 4.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Un estudio retrospectivo publicado en China en 2020 revela que las papilas tipo 2 y 3 requieren más tiempo para la canulación y tienen una tasa más alta de canulación fallida (12 % y 11,1 %) con respecto a las papilas 1 y 4 (1,7 % y 6,25 %) (13) , a diferencia de nuestros resultados, que muestran que los tipos de papila que requirieron más tiempo de aunque no encontramos asociación entre el tipo de papila y la canulación difícil. Por su parte, los tiempos promedio de canulación mostrados en nuestro estudio fueron mayores, sobre todo para el tipo 4.…”
Section: Resultsunclassified
“…La pancreatitis fue el evento adverso más frecuente, con una tasa más alta en el tipo 2 (9,09 %). Este hallazgo fue similar a lo encontrado por Chen y colaboradores, en cuyo estudio la papila de tipo 2 tuvo el mayor porcentaje de pancreatitis pos-CPRE (20 % frente a 6,78 % del tipo 1; 1,59 % del tipo 3 y 6,25 % del tipo 4; p = 0,020) (13) . Haraldsson y colaboradores en 2019 también informaron una mayor tasa de pancreatitis para la papila de tipo 2 (9,4 %), pero sin diferencias significativas con respecto a los otros tipos de papilas (9) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Therefore, identifying factors that predict difficult biliary cannulation during ERCP may help reduce the incidence of PEP in patients with CBDS. Although previous reports have revealed that malignant biliary strictures are a risk factor for difficult cannulation [ 21 , 22 ], only a few studies have focused on factors predicting difficult biliary cannulation in patients with CBDS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nonagenarians require more ERCP procedures to eliminate bile duct stones [ 22 ]. In addition, the higher proportion of tumors in elderly patients, especially ampullary carcinoma, resulted in difficult cannulation [ 23 ], which was known as a factor for post-ERCP complications [ 21 ]. Age and multiple comorbidities are also associated with increased odds of inpatient mortality in patients undergoing ERCP [ 16 ].…”
Section: Discussionmentioning
confidence: 99%